Integration of augmented reality in sleeve packaging for food industry / Zulaikha Zainal - Zainal, Zulaikha (Universiti Teknologi MARA, Perak, 2020)
Twelve Slices Cafe is a bakery business that sells bread, dessert, and traditional cakes. Its products are regularly ordered as a celebratory dish for events such as weddings and birthdays. Besides that, it also offers a food delivery service. However, products sold formerly were packed in just plastic bags. Therefore, unique packaging is needed to enhance product visibility and branding. The purpose of this project is to introduce a sleeve packaging that adds handle-carrier to its newly defined concept shape. Not only it would differentiate the café’s products from its competitors, but the significant design of the packaging would also attract their target market. Furthermore, after a thorough exploration of creative design and evaluation, sleeve packaging is selected as the most suitable type of packaging for the cafe’s range of products. This type of packaging will reduce the use of plastic, and it could also display the product visually. Information on the packaging will also help to convince consumers of the quality of the products. Moreover, the integration of augmented reality in the innovative printed-based packaging would also improve customers’ experience.